2010
DOI: 10.1080/00288306.2010.500320
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of arsenic by iron rich precipitates from two coal mine drainage sites on the West Coast of New Zealand

Abstract: Dissolved As can be strongly adsorbed to fine grained Fe(III) minerals such as hydroxides, oxyhydroxides and hydroxysulphates. Therefore precipitates that form during neutralisation or treatment of acid mine drainage have potential to be useful for treatment of As-contaminated water because acid mine drainage is often Fe rich. We tested the adsorption properties of Fe(III) rich precipitates from two West Coast coal mines with As-contaminated water from an historic gold ore processing site near Reefton. Precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
(39 reference statements)
0
3
1
Order By: Relevance
“…Fitting by the Langmuir model provides maximum As(V) adsorption capacities (q m ) for MIRESORB TM and GFH of 50.38 mg/g and 29.07 mg/g, respectively. The q m for the MIRESORB TM was higher than that reported in similar previous studies of AMDS, in which the As(V) adsorption capacity of AMDS was approximately 10-70 mg/g and varied with AMDS characteristics and experimental conditions [29][30][31]. A composite AMDS with organic binder material showed slightly decreased adsorption capacity.…”
Section: Effect Of Phcontrasting
confidence: 56%
“…Fitting by the Langmuir model provides maximum As(V) adsorption capacities (q m ) for MIRESORB TM and GFH of 50.38 mg/g and 29.07 mg/g, respectively. The q m for the MIRESORB TM was higher than that reported in similar previous studies of AMDS, in which the As(V) adsorption capacity of AMDS was approximately 10-70 mg/g and varied with AMDS characteristics and experimental conditions [29][30][31]. A composite AMDS with organic binder material showed slightly decreased adsorption capacity.…”
Section: Effect Of Phcontrasting
confidence: 56%
“…The removal of arsenic concomitantly to Fe, so called "natural attenuation", has been 393 described in several AMD throughout the world (e.g. Cheng et al, 2009;Rait et al, 2010;394 Paikaray, 2015). In AMD, arsenic is generally removed from the dissolved phase by sorption 395 onto schwertmannite (Carlson et al, 2002;Fukushi et al, 2003;Ohnuki et al, 2004) or 396 formation of amorphous ferric arsenate (Maillot et al, 2013).…”
Section: Arsenic Removal 392mentioning
confidence: 99%
“…The precipitates produced in laboratory bioreactors treating synthetic Lopérec mine water were composed of 2-line ferrihydrites with a few diffraction peaks indicating the presence of crystallized Fe(III) products, mainly hematite and goethite [22]. Ferrihydrite and goethite are both know to remove As by co-precipitation and adsorption in acidic waters [42] and by adsorption in neutral waters [43]. In contrast with Fe, As was immediately removed, certainly because the Fe/As ratio is more than enough to remove all As even if Fe precipitation was not complete.…”
Section: As and Fe Removalmentioning
confidence: 99%
“…Average dissolved As/Fe ratio in Lopérec water is 22.9 mg.g −1 . Rait et al [43] have shown that by adsorption only, Fe can remove arsenic up to 12 mg.g −1 in circumneutral water and up to 74 mg.g −1 in acidic water. Sekula et al [44] showed that ochreous precipitate from a circumneutral mine drainage contained up to 69 mg.g −1 As.…”
Section: As and Fe Removalmentioning
confidence: 99%